PENGGUNAAN BALOK CUISENIARE UNTUK MEDIA PENGENALAN BILANGAN BAGI ANAK USIA DINI - Umayah Umayah; Juhri Juhri; Birru Muqdamien; Wulan Fauzia; Siti Mintani Maulida Qolbiyah (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2021)
Learning activities carried out in RA Al-Istiqomah still have children who have difficulty to say or list the numbers 1 to 10, children have difficulty in pointing with objects, children have difficulty making sequences of numbers 1 to 10 using objects, children have difficulty showing symbols numbers 1 to 10, children have difficulty in recognizing many objects slightly the same and not the same thing. Children have difficulty showing 2 sets of objects that are equal in number, which are not the same, more and less. Teaching numerals to children requires interesting media for children, the success of early childhood learning is influenced by the media used, one of the stimulations that need to be done to stimulate children's ability to say is to introduce numbers to early childhood. To introduce numbers in early childhood to feel happy and interested, it is necessary to apply the right media, one of which is playing the Cuisenaire beam. The purpose of this study was to describe about 1) Knowing the learning of Cuisenaire beam game tools in spelling on RA Al-Istiqomah group A. 2) Knowing the ability to say at RA Al-Istiqomah group A after being given the actions of the Cuisenaire beam game tool. The method used in this study is classroom action research conducted through two cycles. From the results of evaluations, reflections, and improvements made at the end of the cycle, a description of the use of the Cuisenaire beam props that can improve the ability to say group A follows the steps as follows: a) The teacher prepares the Cuisenauire beam. b) The teacher invites children to play cuiseniare beams with the learning activities that have been determined. c) The teacher guides the child to make two groups, each group consisting of 3 to 4 children. d) The teacher starts the Cuisenaire beam relay game.